RF CMOS transceivers for cellular telephony. - Razavi, B. (IEEE Communications magazine)
This article describes system and circuit issues related to cellular transceivers, presenting design techniques that have provided high performance in CMOS technology. Following an overview of relevant GSM and WCDMA specifications, the article identifies four trends in RF design that have continued to improve the performance. Examples of CMOS transceivers, and circuit and device concepts are then described that meet the stringent requirements of cellular telephony.